Efektivitas Konseling Realitas untuk Mengurangi Nomophobia (No-Mobile Phone Phobia) pada Siswa Kelas IX di SMP Adh Dhuha Jember - Yasinta Nur Izza Riyanto; Weni Kurnia Rahmawati; Nailul Fauziyah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Nomophobia (no mobile-phone phobia), defined as excessive anxiety when individuals are unable to access their smartphones, has become a serious challenge among adolescents, particularly junior high school students growing up in the digital era. Uncontrolled smartphone use may disrupt learning concentration, social relationships, and students’ mental health. Therefore, effective counseling interventions that are relevant to adolescents’ developmental characteristics are needed. This study aimed to evaluate the effectiveness of reality counseling using the WDEP (Wants, Doing, Evaluation, Planning) technique in reducing nomophobia among ninth-grade students at SMP Adh Dhuha Jember. A quantitative approach was employed using a quasi-experimental design with a pre-test–post-test control group model. Participants were selected through purposive sampling, consisting of students identified as having high levels of nomophobia based on pre-test results. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using an independent sample t-test to examine differences in nomophobia levels between the experimental and control groups. The results showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the two groups. The mean score of the experimental group decreased substantially from 88 in the pre-test to 45.38 in the post-test after receiving the reality counseling intervention, whereas the reduction in the control group was less pronounced. These findings demonstrate that reality counseling with the WDEP technique is effective in reducing nomophobia among junior high school students. This study provides important practical implications for school guidance and counseling services in designing interventions that are responsive to adolescents’ digital behavior problems in the technology-driven era.